Sex Hormones and Prognosis of Neonatal Seizures - J Gordon Millichap (Pediatric Neurology Briefs)
The influence of testosterone on the development of the substantia nigra pars reticulata (SNR), a brain region involved in the control of seizures, was investigated in male rats castrated at birth, in experiments at Albert Einstein College of Medicine and Montefiore Medical Center, Bronx, NY.